2011
DOI: 10.1007/s10461-010-9871-0
|View full text |Cite
|
Sign up to set email alerts
|

Reluctance to Do Blood Testing Limits HIV Diagnosis and Appropriate Health Care of Sub-Saharan African Migrants Living in Spain

Abstract: This study investigates the reasons why sub-Saharan African migrants (SSAM) living in Spain may be unwilling to have their blood tested. A qualitative study was developed for 3 years (2006-2009) with the participation of 1338 SSAM. Cultural differences along with lack of information about Spanish health care system and health-related rights produced a feeling of mistrust towards medical staff. Reluctance to do blood testing may prevent SSAM from having a prompt HIV diagnosis and an appropriate health care. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 8 publications
1
39
0
2
Order By: Relevance
“…Feeling healthy, lack of symptoms, and lack of preventive healthcare were barriers to HIV testing across the board [8,11,16,28,41,51,52]. It was identified that African migrants' contact with traditional medicine in their home country was usually greater than that with western medicine, and this acted as a barrier in the receiving country [52].…”
Section: Knowledge Attitudinal and Behaviouralmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeling healthy, lack of symptoms, and lack of preventive healthcare were barriers to HIV testing across the board [8,11,16,28,41,51,52]. It was identified that African migrants' contact with traditional medicine in their home country was usually greater than that with western medicine, and this acted as a barrier in the receiving country [52].…”
Section: Knowledge Attitudinal and Behaviouralmentioning
confidence: 99%
“…It was identified that African migrants' contact with traditional medicine in their home country was usually greater than that with western medicine, and this acted as a barrier in the receiving country [52]. African migrant participants noted self-medicating and waiting until extremely sick before seeking ''formal'' healthcare [53].…”
Section: Knowledge Attitudinal and Behaviouralmentioning
confidence: 99%
“…In view of these data, we believe that the current screening of HIV infection [30] is not sufficient to achieve control of the epidemic. Prevention campaigns are necessary and should be oriented at increasing the perception of risk in the general population (heterosexual transmission) and among the sub-Saharans [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these populations often do not seek medical care until they feel ill [5]. The subSaharans constitute an especially vulnerable population, with a poor education level, greater lack of knowledge about the health system and stigmatization [23].…”
Section: Mortalitymentioning
confidence: 99%
“…Thus, we hope to reduce barriers to health services related to distrust of healthcare professionals. Regarding blood testing, previous experiences of SSAM with healthcare systems both in Africa and Spain influenced the perception of blood testing as a potentially unhealthy and abusive practice 9 . Reluctance to undergo blood testing was hampering patients' medical follow-up while increasing barriers for HIV testing and treatment.…”
mentioning
confidence: 99%